2019
DOI: 10.1097/hjh.0000000000001850
|View full text |Cite
|
Sign up to set email alerts
|

Early central blood pressure elevation in adult patients with 21-hydroxylase deficiency

Abstract: We found an early rise in central SBP in CAH patients whereas sublinical arterial damages markers were normal. Our study suggest that vascular damages and increased cardiovascular risk could be mainly BP-driven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…There have been many studies on CAH that indicate an increased cardiometabolic risk, including insulin resistance (4,6,81,89,125,137,145,146,147,148,149,150), but very few indicating an increased frequency of established cardiovascular disease (129,151) or diabetes (including gestational diabetes) (81,103,151). Since most studies have been performed in children and adolescents and most of the adults in the CAH studies have been aged less than 50 years, this is to be expected because cardiovascular disease and diabetes usually develop later in life (64).…”
Section: Cardiovascular Disease and Diabetesmentioning
confidence: 99%
“…There have been many studies on CAH that indicate an increased cardiometabolic risk, including insulin resistance (4,6,81,89,125,137,145,146,147,148,149,150), but very few indicating an increased frequency of established cardiovascular disease (129,151) or diabetes (including gestational diabetes) (81,103,151). Since most studies have been performed in children and adolescents and most of the adults in the CAH studies have been aged less than 50 years, this is to be expected because cardiovascular disease and diabetes usually develop later in life (64).…”
Section: Cardiovascular Disease and Diabetesmentioning
confidence: 99%
“…For every patient with CAH, a healthy control matched for sex, age, and smoking status was prospectively included in the CARDIOHCS study (NCT01807364) between May 2011 and August 2015 (8,9,10). Patients with CAH and healthy controls were all assessed at the Clinical Investigation Center Paris-Est (CIC-1421, Pitie-Salpetriere University Hospital, Paris, France).…”
Section: Study Population and Settingmentioning
confidence: 99%
“…The majority of studies including adults and children with CAH have reported an increased body fat mass assessed by DXA [96,101,102,106,107], which enables separation between lean mass (which may be increased due to hyperandrogenism) from fat mass. Elevated cardiometabolic risk, including insulin resistance [4,94,[108][109][110][111][112][113][114][115][116][117], has been reported in a large number of studies on CAH, with a few reporting increased rate of established cardiovascular disease [103,118], and diabetes (including gestational diabetes) [81,109,118]. Very few individuals with CAH above 50 years of age have been included in studies, and thus it could be expected that the rate will increase since cardiovascular disease and diabetes usually develop later in life [1].…”
Section: Obesity Diabetes and Cardiovascular Diseasementioning
confidence: 99%